Giovanni Chiaromanni and his travel from Vienna to Bursa in 1659 (Colloquia Comparativa Litterarum, 2025)
Penka Danova (Ed. and translation). Giovanni Chiaromanni and his Travel from Vienna to Bursa in 1659.